Improved varieties perform well in realized genetic gain trials with Norway spruce seed sources in southern Sweden. Issue 6 (18th August 2019) - Liziniewicz, Mateusz; Karlsson, Bo; Helmersson, Andreas
ABSTRACT: Genetically improved Norway spruce ( Picea abies L. Karst ) has been extensively used in operational plantations in Sweden. However, there have been few studies that aimed at verifying the realized genetic gain over a longer time span in plots established with one genetical entry. Two experimental series at six sites in southern Sweden, established purely for this purpose, were assessed. Early height growth of 10 Norway spruce seedlots of different genetic levels was compared. There were significant differences in height at the age of 5 and 8 years between improved and unimproved seed sources and the differences between most advanced material from the breeding front, represented by full-sib crossings of selected plus-trees, and unimproved Swedish spruce were 36% and 30% at the age of 5 and 8 years, respectively. At the same ages, the trees originating from the second round of seed-orchards were 25% and 21% higher than unimproved material. There were also about 20% differences between the best and worst tested full-sib families, indicating large possible gain in the new generation. The study confirmed earlier estimates of genetic gain levels of different seed sources in the breeding program for Norway spruce.